Identification Of Termites In Lawang Sewu Heritage Building Semarang City - Thyar Deby Yuhara; Sri Yuliawati; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Termites are known as wood destroying insects and most important building construction wood and other lignocellulosic materials have been reported in almost all of Indonesia. Lawang Sewu is a heritage building where wood components used in the building is teak wood, which is resistant to termite attack. However,preliminary survey results mark the presence of termites in one corner of the building showed a wanderer termite burrows. The purpose of this study is to identify the species of termite that has been obtained in the research and describe the environmental conditions, including temperature and humidity as well as describing the condition of the building. This research is a descriptive study using survey method and cross sectional approach. The population in this study was all termites in the area Lawang Sewu building. The samples in this study were sampled using a total sampling building and termite sampling using accidental sampling technique. From the results of this research note that was found termite species Macrotermes gilvus Hagen major and minor soldiers and Coptotermes curvignathus Holmgren. The temperature ranges between 28.9°C-33°C, relative humidity ranged between 41.6%-89.7%. While the condition of the building there is damage where such damage can lead to termite entry into the building and attack, there are B,D and E building. Therefore, there needs to be a cleansing of wood, trees that have died and other materials contain lignocellulotic which directly related to land, repairing buildings damaged and need an immediately evaluate for termite treatment that has been done